AN ANALYTICAL STUDY OF RURAL ENTREPRENEUR’S PREFERENCE REGARDING SITE SELECTION IN HARYANA - Kavita (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Competing for a perennial supply of inputs is the main factor affecting business units and theoretically, they must be placed at a favorable distance between themselves to get profitability. The location optimized on economic factors seldom corresponds with the actual location of a rural business unit as the final selection as a result of a complicated set of factors, both subjective and objective. This research paper models the impact of different variables on location selection strategies of the rural units in Haryana. Outcomes of the study represent that the demographic variables indicated density of population, literacy rate, and employment strategies emerge as the significant variable related to the selection of a location of rural business units. Out of the subjective factors, the location-oriented and micro variables, comprising of the regulatory system, and the site-specific fixed costs score over the macro variables while selecting a location.